(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Prescription order and information on it; represent the key for reach of safe and effective medications to the patient, and the clarity of its information is important to prevent medications errors that may be lethal to the patient. Objectives: Comparison of samples of prescriptions and their contents of physician; patient related information with standard information provided by WHO prescription writing. Methods: A sample of prescription orders received from private clinics by community pharmacies in Al-Ashar of Basra city. The prescriptions were taken from several pharmacies randomly and about 1000 prescriptions were collected. The prescriptions represent about 40 physicians in different specialties and for a period extended from November 2009 until March 2010. The information of prescriptions were analyzed by simple statistics for calculation the percentage of adherence for WHO guideline in prescription writing. Results: The prescription information includes; prescriber’s name, address, telephone number and signature were on 97.5%, 74.8%, 4.3% and 96.5% of prescriptions respectively. The patient’s name, age and weight were on 96.6%, 15.5% and 2.2%. No prescription contained the patient’s address and gender. The strength of medication and dose units were included in 1.7% and 1.4% of prescriptions. The prescriptions had only quantity indicated 2.4% and more than one third instructions for patient use (36.1%); the diagnosis was not included in more than two-thirds (85.2%). The prescriber’s handwriting was illegible in 16.3% of prescriptions. Conclusions: There is severe deficiency in fitness of prescriptions written by the physician to WHO guidelines; so we recommend for administrative monitoring program for fitness of prescriptions to these guidelines and start education about this guideline for prescribers. Key words: Prescriptions, WHO, prescriber, patient, prescriber’s name, address, telephone number, signature